2016
DOI: 10.1136/bmj.i2161
|View full text |Cite
|
Sign up to set email alerts
|

Should we welcome food industry funding of public health research?

Abstract: Researchers should accept research grants from the food industry, write Paul Aveyard and Derek Yach, but Anna B Gilmore and Simon Capewell say that it biases science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Whether current conflict of interest policies are adequate to withstand the economic interests of industry remains unclear. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Whether current conflict of interest policies are adequate to withstand the economic interests of industry remains unclear. 54 …”
Section: Discussionmentioning
confidence: 99%
“…The optimal role for industry in nutrition research remains unclear 3233. Given the scale of diet related diseases, funding for research on foods and nutrients is limited.…”
Section: Vested Interestsmentioning
confidence: 99%
“…This included two elements: the appropriateness of accepting funds from the food industry and the governance processes for accepting funds. There was a variety of principles related to the appropriateness of accepting funding; these ranged from not accepting any commercial funding to not accepting funding from the food industry or the ultraprocessed food industry . Alternatively, for those who believed it was appropriate to accept funding, some suggested that it should go through an independent, intermediary body, whilst others actively encouraged direct relationships between researchers and the food industry …”
Section: Resultsmentioning
confidence: 99%
“…Kraak and Story and Rowe et al encouraged a more moderate approach for assessing food companies, proposing interactions only with those who share objectives or have a shared approach to the research. Others provided more explicit guidance for assessing potential food companies with which to interact, stating that an interaction should only be initiated if it helps to advance public health goals and that companies selling or promoting unhealthy foods should be avoided …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation